Hilary Mantel 'In Conversation' - audio - Goodman, Martin; Mantel, Hilary (The University of Hull)
The winner of this year's Booker Prize for her novel Wolf Hall, which draws us into Henry VIII's court through the scheming life of Thomas Cromwell, Hilary Mantel is one of the most brilliant and wide-ranging writers of our times. We are delighted to hold this event, in which Hilary Mantel will be discussing (with Martin Goodman) the span and the inspiration for her life's work.